A Prospective Comparative Study on Cardiac Alterations After Surgery and Drug Treatment of Primary Aldosteronism - Yi-Lin Chen (Frontiers Media S.A., 2021)
BackgroundCurrent guideline recommends both surgery and drug treatment for primary aldosteronism. Treatment effects on the cardiac structure and function remain under investigation.ObjectiveWe performed a prospective study in patients with primary aldosteronism to compare effects of surgery and drug treatment on the cardiac structure and function as assessed by the left ventricular (LV) pressure-strain loop, a novel echocardiographic technique that incorporates myocardial deformation and LV pressure.MethodsOur study included 39 and 28 patients treated with surgery and a mineralocorticoid antagonist, respectively. We performed conventional and speckle tracking echocardiography at baseline and 3 and 6 months of follow-up.ResultsDuring follow-up, both surgery and drug treatment normalized serum potassium concentration and significantly reduced blood pressure. Both treatments significantly and similarly decreased LV mass index and left atrial volume index. However, only in the surgery group did global wasted work significantly decrease (200.8 ± 86.7 at baseline vs. 142.1 ± 58.1 mmHg% at 6 months) and global work efficiency (91.5 ± 3.1 vs. 93.6 ± 2.3%) and global longitudinal strain (−18.3 ± 2.7 vs. −19.2 ± 1.9%) significantly (p < 0.01) increase at 6 months of follow-up. The corresponding differences from the changes in the drug treatment group were 39.5 mmHg% (95% CI, 17.1, 62.0 mmHg%), −1.64% (95% CI, −2.56, −0.71%), and −0.85% (95% CI, −1.51, −0.20%), respectively. In addition, the changes in global wasted work at 6 months of follow-up was significantly correlated with that in 24-h urinary aldosterone excretion in the drug treatment group (r = 0.54) and two groups combined (r = 0.55), but not the surgery group.ConclusionIn spite of similar serum potassium normalization and blood pressure control, surgical removal of an adrenal gland, but not mineralocorticoid receptor antagonism, showed early improvement in cardiac function.